Chemically converting residual lithium to a composite coating layer to enhance the rate capability and stability of single-crystalline Ni-rich cathodes. (April 2022) - Du, Ya-Hao; Sheng, Hang; Meng, Xin-Hai; Zhang, Xu-Dong; Zou, Yu-Gang; Liang, Jia-Yan; Fan, Min; Wang, Fuyi; Tang, Jilin; Cao, Fei-Fei; Shi, Ji-Lei; Cao, Xiu-Fang; et al.
Abstract: Single-crystalline Ni-rich cathodes express great potential in state-of-the-art lithium-ion batteries (LIBs), but they still suffer from severe surface reactions, sluggish kinetics and microcracks upon prolonged cycling. Coating is an efficient strategy, yet the smooth morphology and low surface energy make it difficult to obtain a high-quality coating layer. In addition, most of the coatings hinder the interfacial transport of Li +, which further exacerbates the inherent sluggish kinetics of the single-crystalline cathodes. Here, assisted by reactive wetting of the residual lithium, a phospholipid-like protective layer of AlPO4 -Li3 PO4 is successfully constructed on the single-crystalline LiNi0.8 Co0.1 Mn0.1 O2 surface (SC@ALP), in which the ionic conductor Li3 PO4 accelerates interfacial Li + transport and the amorphous AlPO4 relieves stress during cycling. The obtained composite SC@ALP cathode shows excellent cycling stability (88.9% capacity retention after 200 cycles) and rate capability (160.8 mA h g −1 at 3 C). This bifunctional coating strategy provides a new avenue for surface modification and may accelerate the development of single-crystalline Ni-rich cathodes for next-generation LIBs. Graphical Abstract: The phospholipid-like protective layer of AlPO4 -Li3 PO4 is successful constructed on single-crystalline LiNi0.8 Co0.1 Mn0.1 O2 surface. On the one hand, the amorphous AlPO4 can protect the particle surface from the attack of detrimental species generated by electrolyte decomposition. On the other hand, the crystalline Li3 PO4 acts as a selective channel which can allow only the transference of Li + . The two functional species work synergistically just like the mechanism of the phospholipid bilayer of a cell. ga1 Highlights: The phospholipid-like protective layer of AlPO4 -Li3 PO4 is successfully constructed on single-crystalline surface. The amorphous AlPO4 can protect the particle surface from the attack of detrimental species generated by electrolyte decomposition. The crystalline Li3 PO4 acts as a selective channel which can allow only the transference of Li + . The as-obtained cathode shows excellent rate capability and stability.